Zero-field quantum beats and spin decoherence mechanisms in CsPbBr₃ perovskite nanocrystals - Cai, Rui (2023)
Coherent optical manipulation of exciton states provides a fascinating approach for quantum gating and ultrafast switching. However, their coherence time for incumbent semiconductors is highly susceptible to thermal decoherence and inhomogeneous broadening effects. Here, we uncover zero-field exciton quantum beating and anomalous temperature dependence of the exciton spin lifetimes in CsPbBr3 perovskite nanocrystals (NCs) ensembles. The quantum beating between two exciton fine-structure splitting (FSS) levels enables coherent ultrafast optical control of the excitonic degree of freedom. From the anomalous temperature dependence, we identify and fully parametrize all the regimes of exciton spin depolarization, finding that approaching room temperature, it is dominated by a motional narrowing process governed by the exciton multilevel coherence. Importantly, our results present an unambiguous full physical picture of the complex interplay of the underlying spin decoherence mechanisms. These intrinsic exciton FSS states in perovskite NCs present fresh opportunities for spin-based photonic quantum technologies.